2020
DOI: 10.2147/imcrj.s274140
|View full text |Cite
|
Sign up to set email alerts
|

<p>Panophthalmitis and Orbital Inflammation with Cavernous Sinus Thrombosis Following Cataract Surgery</p>

Abstract: Background Panophthalmitis is a severe inflammation of the globe that can result as a rare complication of ophthalmic surgery. In severe cases, it may also be associated with orbital inflammation and cavernous sinus thrombosis. Purpose This case demonstrates a rare and life-threatening post-operative complication of cataract surgery. We also hope to highlight the importance of considering the relevant risk factors associated with developing potential infections after ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Cases complicated by globe rupture or perforation, or intractable pain or infection are treated with evisceration or enucleation. Possible complications of untreated infection include orbital abscess, superior ophthalmic vein or cavernous sinus thrombosis, meningitis, or encephalitis [1] , [5] , [6] , [7] , [8] . Chen et al concluded that multiple intravitreal treatments may be associated with lower likelihood of requiring evisceration or enucleation [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Cases complicated by globe rupture or perforation, or intractable pain or infection are treated with evisceration or enucleation. Possible complications of untreated infection include orbital abscess, superior ophthalmic vein or cavernous sinus thrombosis, meningitis, or encephalitis [1] , [5] , [6] , [7] , [8] . Chen et al concluded that multiple intravitreal treatments may be associated with lower likelihood of requiring evisceration or enucleation [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous panophthalmitis can be from hematogenous spread of the pathogen, while exogenous panophthalmitis occurs as a consequence of ocular penetration (e.g. trauma or surgery) [ 2 ]. The case reported here is unusual in that panopthalmitis resulted from direct extension from the orbit into the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evisceration or enucleation of the globe can be done for rapidly progressing cases with no visual potential [ 5 ]. Enucleation can be especially useful in preventing and controlling life-threatening sepsis [ 2 ]. Due to the progressive nature of the disease, lack of visual potential, and the concern for other serious complications, enucleation was performed in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation